Ethnocoreology and Storytelling: New Forms of Hybridization in Art. 50 shades of "fucking storytelling” - Del Marco, Vincenza (E|C, 2020)
Space selfies are reflective shots, object of sharing, made in space. Even before the spread of the expression, images of this form have been made, some of them using the visor of another astronaut's helmet as a mirror. Among them are photographs made by astronauts or machines, such as robot selfies or rover selfies. The intervention intends to analyze a corpus of images of this field to develop reflections on the relationship between narration, life forms, and technologies, even by an epistemological point of view, with a focus on the visual issue. Among others, it will be considered the selfie ante-litteram realized by astronaut Buzz Aldrin in November 1966 and the release of the Japanese astronaut Aki Hoshide, one of the most famous in the general selfie charts of 2013. During an exit from International Space Station for repair, along with American Sunita Williams, has made photos with a digital reflex, specially designed to withstand adverse space conditions. It will also be considered some shots shared on social networks by Samantha Cristoforetti and will be examined some images of Curiosity Mars, the automatic robot that is exploring the planet since 2012, commonly defined by NASA and in the intermedial sphere as selfie.